Changes in secondary metabolites in soybean (Glycine max L.) roots by salicylic acid treatment and their anti-LDL oxidation effects - Kim, Jeong Ho; Shah, Abdul Bari; Lee, Yong Hyun; Baiseitova, Aizhamal; Ban, Yeong Jun; Park, Ki Hun (Frontiers in Plant Science, 2022)
Abundance of metabolites in plant is a critical factor toward being functional food stuff. Salicylic acid (SA) treatment led significant changes in levels of the secondary metabolites in soybean roots. Notably, the exposure of 3 mM of SA aqueous solution to soybean plants for 24 h resulted in distinctive increases in the levels of coumestrol (16-fold, 0.3 → 4.8 mg/g) and daidzein (7-fold, 1.2 → 8.9 mg/g) in roots part. These changes were systematically investigated by LC-ESI-TOF/MS analysis to afford a clear difference of PLS-DA score, heatmap, and box plots. Quantitative analysis showed that SA treatment played to stimulate biosynthesis of coumestrol as well as hydrolysis of its glycosides (coumestrin and malonylcoumestrin). The highly improved anti-LDL oxidation effect was observed in the SA treated soybean roots in the three different assay systems. It might be rationalized by the increased levels of coumestrol and daidzein.